Gender differences in continuous-flow left ventricular assist device therapy as a bridge to transplantation: a risk-adjusted comparison using a propensity score-matching analysis - Weymann, Alexander; Patil, Nikhil Prakash; Sabashnikov, Anton; Mohite, Prashant N.; Sáez, Diana García; Amrani, Mohamed; Bahrami, Toufan; Robertis, Fabio De; Wahlers, Thorsten; Banner, Nicholas R.; Popov, Aron-Frederik; Simon, André R. (Artificial organs, 2015)
The purpose of this study was to evaluate gender differences regarding outcome after continuous-flow left ventricular assist device (cfLVAD) implantation. The study was a retrospective review of prospectively collected data. Included were 24 consecutive female cfLVAD recipients and 24 male recipients (62.5% HeartMate II, 37.5% HeartWare) who received their devices between July 2007 and May 2013. Subjects were matched using propensity score analysis based on age, diagnosis, body surface area, preoperative mechanical circulatory support, heart failure severity score (INTERMACS class), and comorbidities. Female patients were significantly sicker before operation. After propensity score matching, there were no statistically significant differences in demographics or clinical baseline characteristics between male and female LVAD recipients. Also, there was a trend towards a longer postoperative intensive care unit stay in the female group (median 9 days [interquartile range 5-17] versus 15 days [interquartile range 8-33]; P < 0.061) and higher postoperative bilirubin values (median 14 mmol/L [interquartile range 10-17] versus 21 mmol/L [interquartile range 13-30]). However, there were no significant differences between the two groups in terms of outcome (P < 0.569). The overall survival was comparable between the two groups (log rank P < 0.389). Half (50%) of female patients required inotropic support for more than 7 days compared with 21.7% in the male group (P < 0.048). Half (50%) of female recipients required short-term postoperative right ventricular assist device implantation compared with 16.7% in the male group (P < 0.014). In conclusion, cfLVAD implantation as a bridge to transplantation is associated with longer duration of inotropic support and higher requirement for postoperative mechanical right ventricular support in women with similar survival rates. Further studies are required to identify additional demographic and clinical factors that modulate outcomes and will enhance the ability to risk-stratify cfLVAD recipients.
First published: 29 August 2014
Gesehen am 01.07.2020